The Appropriation of Sidewalks For E-Scooter; From The Urban Built Environment Perspective - Rachmanto, Adinda Smaradhana (UI Scholars Hub, 2021)
One of the most popular types of micromobility that has rapidly grown in Europe for some recent years is an electric scooter (e-scooter). An emerging phenomenon occurred in many places, including Stockholm. Regardless of some positive claims about e-scooters in urban areas, e-scooters also contribute to new urban problems. Some of the problems occurred in the sidewalk environment, and those issues are widely discussed among pedestrians. Therefore, this study will investigate how the presence of e-scooters affected the pedestrian around Stockholm inner-city based on the experience of various groups of people that use sidewalk environments, including pedestrian and e-scooter users. The finding showed that various perspectives occurred while experiencing e-scooters in the sidewalk environment. Some of the experiences also affected their decisions to walk on the sidewalks. This study expected to add some understanding of how humans perspective on perceiving new materials in their built environment could add value in the planning and design process for the sidewalk environment in the future.